ANALYZE THE FACTORS THAT INFLUENCE JOB PROMOTION AT DINAS PEMUDA DAN OLAHRAGA (DISPORA) PROVINSI SULAWESI UTARA - Lahia, Bonifasius J.; Pangemanan, Sifrid S.; Arie, Fitty Valdi (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
Human resources are an important factor in every company's activity, because no matter how sophisticated the technology used, without human resources to support its operational personnel, it is impossible to produce output that is in accordance with the expected level of efficiency. This study is aim to know the factors that influence job promotion. This research is quantitative type of research which uses primary data obtained through questionnaire and uses Confirmatory Factor Analysis (CFA) as the analytical tool. The population of this research is the employee at Dinas Pemuda dan Olahraga (DISPORA) Provinsi Sulawesi Utara, where the sample size is taken from 74 workers. In this research, there are 20 variables that defined as factors that influence job promotion at DISPORA. There are 20 variables that included in the analysis, and the result show that there are 3 variables is not qualified, and the most dominant factors based on communality test are Merit (0.762), followed by Experience (0.749), Work Achievement (0.747), Attitude (0.737), and Work Attendance (0.731). The researcher recommends for the employee in DISPORA to improve their job especially the five factors that dominant and for the company to improve their Human resources management.Â Keywords: Job Promotion